In Pacific waters - Palmer, George Archibald (Conquest series)
Lesson I. Here and there in the Hawaiian Island. Obookiah. -- Lesson II. What the missionaries found. A bit of Hawaiian history. -- Lesson III. Ninety years after. A home mission field. A pull all together.